The shape of rain - Koep, Michael B. (Koep, Michael B. Newirth mythology, 2018)
"Discredited mythology professor Astrid Finley believes gods and immortals once battled for a place in creation--for a place of their own on the earth. When she is summoned to a secret archaeological dig site in Northern Idaho to translate an ancient script, she uncovers an unthinkable nightmare--a woman buried alive for over a thousand years. Meanwhile, Loche Newirth's assassination is ordered to prevent him from rewriting history. But his former mentor Dr. Marcus Rearden wants him alive to torture, to command, to control. When Loche discovers his son is also a target, he flees, pursuing a lead that promises to end what his writing has started. Instead, the path vaults him back to the prehistory of the story--to a time when a venomous army of gods lay siege to the City of Immortals, and his little boy stands in the balance"--Jacket flap.